Methods for Improving In Vitro and In Vivo Boar Sperm Fertility. (July 2015) - Funahashi, H
Contents: Fertility of boar spermatozoa is changed after ejaculation in vivo and in vitro . During processing for in vitro fertilization (IVF), although spermatozoa are induced capacitation, resulting in a high penetration rate, persistent obstacle of polyspermic penetration is still observed with a high incidence. For artificial insemination (AI), we still need a large number of spermatozoa and lose a majority of those in the female reproductive tract. Fertility of cryopreserved boar spermatozoa is still injured through freezing and thawing process. In the present brief review, factors affecting fertility of boar sperm during IVF, AI and cryopreservation are discussed in the context of discovering methodologies to improve it.